Lights emitting diode on plant growth and photomorphogenesis in Brassica chinensis - Nurul Najwa Ani @ Mahbar, 1987-, author; Robiah Ahmad, Assoc.Prof.Dr., supervisor; Che Radziah Che Mohd. Zain, Dr., supervisor; Sekolah Razak UTM dalam Kejuruteraan Teknologi Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2015)
Thesis